Constraints of Biosecurity Adoption on Beef Cattle Farms - Sri Lestari, Veronica; Sirajuddin, Sitti Nurani; Abdullah, Agustina (European Journal of Sustainable Development, 2018)
Biosecurity is very important to be applied in the farm in order to prevent cattle from contagious diseases. The aim of this research was to know the level and constraints of biosecurity adoption by beef cattle farms in South Sulawesi. This research was conducted in 2017 in Luwu regency, South Sulawesi province. Total sample was 31 beef cattle farmers who were choosed through purposive sampling. Data on biosecurity adoption level included vaccination, sanitation and traffic arrangements. Data were obtained through observation and interview using questionnaire. There were 21 questions for the level of biosecurity adoption. If beef cattle farmers adopt biosecurity, the score was 1, on the other hand, if beef cattle farmers do not adopt biosecurity, the score was 0. To know the adoption barrier, Delphi method and Focus Discussion Group were used. Data were analyzed descriptively. The results showed that the adoption level of beef cattle breeders was categorized as "high adopter". Factors inhibiting the application of biosecurity to beef cattle farmers sequenced from the highest percentage were shortage of extension workers, shortage of veterinarian, lack of technical knowledge of animal husbandry and lack of capital. Keywords: adoption, beef cattle farmers, biosecurity, constraints